Internet of things (IoT)-based unmanned intelligent street light using renewable energy. Issue 1 (12th January 2021) - Anguraj, Dinesh Kumar; Balasubramaniyan, S.; Saravana Kumar, E.; Vakula Rani, J.; Ashwin, M.
Abstract : Purpose: The purpose of the research is to concentrate on the most important smart metropolitan applications which are smart living, smart security and smart maintainable. In that, Power management and security is a most important problem in the current metropolitan situation. Design/methodology/approach: A smart metropolitan area utilizes recent innovative technologies to improve its living, security and maintainable. The aim of this study is to recognize and resolve the difficulties in metropolitan area applications. Findings: The main aim of this study is to reduce the metropolitan foremost energy consumption, to recharge the electric vehicles and to increase the lifetime of smart street lights. Originality/value: The hybrid renewable energy street light applies smart resolutions to substructure and facilities in rural and metropolitan areas to create them well. This study will be applying smart metropolitan solar and wind turbine street light using renewable energy for existing areas. In future, the smart street light work will be implemented everywhere else.